Measurement of redshift-space two- and three-point correlation of Lyα absorbers at 1.7 < z < 3.5: implications on evolution of the physical properties of IGM. Issue 1 (22nd October 2021) - Maitra, Soumak; Srianand, Raghunathan; Gaikwad, Prakash
ABSTRACT: We present redshift-space two-point (ξ), three-point (ζ), and reduced three-point ( Q ) correlation of Lyα absorbers (Voigt profile components having H i column density, N H  i > 10 13.5  cm −2 ) over three redshift bins spanning 1.7 < z < 3.5 using high-resolution spectra of 292 quasars. We detect positive ξ up to 8  h −1  cMpc in all three redshift bins. The strongest detection of ζ = 1.81 ± 0.59 (with Q  = 0.68 ± 0.23) is in $z$  = 1.7–2.3 bin at 1–2  h −1  cMpc. The measured ξ and ζ values show an increasing trend with N H  i, while Q remains relatively independent of N H  i . We find ξ and ζ to evolve strongly with redshift. Using simulations, we find that ξ and ζ seen in real space may be strongly amplified by peculiar velocities in redshift space. Simulations suggest that while feedback, thermal and pressure smoothing effects influence the clustering of Lyα absorbers at small scales, i.e. <0.5  h −1  cMpc, the H i photoionization rate (ΓH i ) has a strong influence at all scales. The strong redshift evolution of ξ and ζ (for a fixed N H i cut-off) is driven by the redshift evolution of the relationship between N H i and baryon overdensity. Our simulation using best-fitting ΓH i ($z$ ) measurements produces consistent clustering signals with observations at $z$ ∼ 2 but underpredicts the clustering at higher redshifts. One possible remedy is to have higher values of ΓH  i at higher redshifts. Alternatively the discrepancy could be related to non-equilibrium and inhomogeneous conditions prevailing during He ii reionization not captured by our simulations.